Development of thermohydraulic models of core elements of “Neutron source” - Kukhotsky, O.V.; Nosovsky, A.V.; Dybach, O.M. (Вопросы атомной науки и техники, 2017)
This article focuses on the development of independent thermohydraulic models of the core elements of the research nuclear subcritical facility. Its design and construction is currently being implemented by the National Science Center “Kharkov Institute of Physics and Technology”. The article describes the process of modeling neutron-generating target and the fuel assembly of “Neutron Source”. Moreover, the results of the verification calculations of the developed models are also clarified. These models are unique, because they were made for the first time for the key elements of subcritical facility using CFD code ANSYS CFX. Описано розробка незалежних теплогідравлічних моделей елементів активної зони дослідницької ядерної підкритичної установки (ЯПУ). Її проектування і спорудження в даний час здійснюється Національним науковим центром «Харківський фізико-технічний інститут». У роботі представлено опис процессу моделювання нейтроноутворюючої мішені і тепловиділяючої збірки ЯПУ «Джерело нейтронів». Висвітлено також результати тестово-верифікаційних розрахунків розроблених моделей, які є унікальними, так як виконані вперше для критичних елементів підкритичної установки з використанням CFD-коду ANSYS CFX. Описана разработка независимых теплогидравлических моделей элементов активной зоны исследовательской ядерной подкритической установки (ЯПУ). Ее проектирование и сооружение в настоящее время осуществляется Национальным научным центром «Харьковский физико-технический институт». В работе представлено описание процесса моделирования нейтронообразующей мишени и тепловыделяющей сборки ЯПУ «Источник нейтронов». Освещены также результаты тестово-верификационных расчетов разработанных моделей, которые являются уникальными, так как выполнены впервые для критических элементов подкритической установки с использованием CFD-кода ANSYS CFX.